Formula and production process of aluminum oxide foamed ceramic product

Through specific formulas and processes, alumina foam ceramic products with improved thermal shock resistance were prepared, which solved the problem of poor thermal shock resistance and stability of existing products in high-temperature use, and achieved a significant improvement in the high-temperature strength and service life of the product.

CN119683973APending Publication Date: 2025-03-25ADTECH METALLURGICAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909560.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing alumina foam ceramic products have poor thermal shock resistance and are prone to cracking and crushing during high-temperature use, which affects the production efficiency and product quality of the aluminum processing industry.

Method used

Specific formulas and processes are adopted, including the use of alumina particles with more than 1,000 mesh, nano-scale silicon micro powder, potassium feldspar powder and mixed rare earth powder, and mixed steps of ball mill mixing, extrusion molding, drying and sintering to prepare alumina foam ceramic products with improved thermal shock resistance.

Benefits of technology

It significantly improves the high-temperature compressive strength, flexural strength and thermal cycle times of alumina foam ceramic products, avoids cracking and crushing, and improves the service life of the product and the production efficiency of the aluminum processing industry.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum oxide foamed ceramic production, and particularly relates to an aluminum oxide foamed ceramic product formula and a production process, and the aluminum oxide foamed ceramic product formula comprises a dry material, a binding agent and a solvent; the dry material comprises alpha-aluminum oxide, activated aluminum oxide, kaolin, silica powder, a dispersing agent, mixed rare earth powder and potassium feldspar powder; the binding agent is aluminum dihydrogen phosphate or silica sol, and the solvent is purified water; the aluminum oxide foamed ceramic product produced by the invention has the advantages that the normal-temperature compressive strength is greater than or equal to 1.0 MPa, the high-temperature (750 DEG C) breaking strength is greater than or equal to 0.7 MPa, the thermal cycle times at 750 DEG C reach 8 casting times, and the aluminum oxide foamed ceramic product has good high-temperature strength, thermal shock resistance stability and metal scouring resistance, and can be widely applied to the field of metal casting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alumina foam ceramic production, and in particular, relates to an alumina foam ceramic product formula and a production process. Background Art

[0002] Foam ceramic filters are widely used in the field of metal melt casting due to their unique three-dimensional interconnected mesh skeleton structure, strong adsorption capacity, low filtration resistance, and high filtration efficiency. With the high-end development of aluminum and other metals, they have great market potential in the metal melting and casting industry. In particular, they can effectively filter out large slag inclusions and micron-level (10-40mm) fine inclusions in aluminum liquid through the filter cake effect, deep bed effect, and rectifying slag effect. By reducing the number of effective crystal nuclei in the molten metal, the molten metal can be nucleated and grown under relatively large supercooling conditions, which refines the grain structure, reduces defects in the alloy, and significantly improves the quality of castings.

[0003] At present, commonly used foam ceramic filter materials include A1203, ZrO2, SiC, silicon nitride, etc., which are used in different fields of metal melt filtration. Among them, alumina foam ceramic products are mainly used in aluminum and aluminum alloy melt filtration, and the operating temperature is about 700-800℃. The use conditions of metal melt filters are quite harsh, requiring the filter medium to have sufficient high temperature strength, thermal shock stability and metal scouring resistance, and not to react with the melt at high temperature. However, in the current market, alumina foam ceramic products have poor thermal shock stability, which leads to cracking and breaking during high-temperature use, causing losses to the aluminum processing industry. Therefore, how to improve the thermal shock resistance of alumina foam ceramic products has become the key to high-end products. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a formula of an alumina foam ceramic product, including a dry material, a binder and a solvent.

[0005] The dry material includes α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder and potassium feldspar powder; the binder is aluminum dihydrogen phosphate or silica sol, and the solvent is pure water; the dry material includes 40-60% of α-alumina, 10-20% of activated alumina, 1-5% of kaolin, 1-5% of silica powder, 0.5-2.5% of dispersant, 5-10% of mixed rare earth powder and 5-10% of potassium feldspar powder by weight. Based on the weight of the dry material, the binder is 30-50% of the weight of the dry material, and based on the weight of the dry material, the solvent is 10-20% of the weight of the dry material.

[0006] Furthermore, the particles of a-alumina are micro-powder-grade particles, and the particle size is 1000-2000 meshes.

[0007] Furthermore, the particle size of the activated alumina is 1000-2000 mesh.

[0008] Furthermore, the particle size of kaolin is 500-1000 mesh.

[0009] Furthermore, the silicon micropowder particles are nano-scale particles, and the purity of the silicon micropowder is greater than 99%.

[0010] Furthermore, the particle size of the dispersant is 500-1000 mesh, and the dispersant is dispersant N or sodium silicate.

[0011] Furthermore, the particle size of the potassium feldspar powder is 500-2000 mesh.

[0012] Furthermore, the particle size of the mixed rare earth is 1000-2000 mesh, and the purity of the mixed rare earth is greater than 99%.

[0013] Furthermore, the mixed rare earth powder is any two of cerium oxide, yttrium oxide and lanthanum oxide, and the mixing ratio by weight is 1:1.

[0014] The present invention also provides an alumina foam ceramic product production process based on an alumina foam ceramic product formula, comprising the following steps:

[0015] S1, Mixture Preparation:

[0016] The weighed α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder, potassium feldspar powder, binder and solvent are sequentially fed into a ball mill, and mixed and ground in the ball mill at room temperature for 2 hours to obtain a mixture;

[0017] S2, Molding:

[0018] The mixed material obtained in step S3 is poured into a pulping machine, and a molded part is obtained by pulping and molding;

[0019] S3, Drying:

[0020] Place the molded parts in an oven to dry, keeping them at 60-120°C for 4 hours;

[0021] S4, sintering:

[0022] The dried molded parts are transferred to a sintering furnace for sintering, and kept at 1000-1300°C for 5-6 hours to obtain finished parts.

[0023] The working principle of the present invention:

[0024] The main raw material in the formula is alumina particles with a mesh size of 1000 or above, which improves the fineness and uniformity of the mixture; the use of nano-scale silicon powder reduces the sintering temperature of the mixture, promotes liquid-phase sintering of the mixture, improves the surface strength of the product, and makes the surface of the product smoother; the role of potassium feldspar is to shorten the drying time of the green body and reduce the shrinkage and deformation of the molded parts caused by drying. After high-temperature melting, it decomposes to form white garnet (K[AlSi206]) and silica glass, which can fill the gaps between the green body particles to improve the thermal shock resistance of the product; the mixed rare earth can react with the binder aluminum dihydrogen phosphate to form aluminum rare earth acid salts, which has an enhancing effect on the strength of the filter plate product. In addition, rare earth oxides can promote particle rearrangement, improve the wettability of particles, fill the pores between particles, and passivate cracks, thereby enhancing the thermal shock resistance of the product.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The process of the invention is simple and the preparation is convenient. The alumina foam ceramic product produced by the invention has a room temperature compressive strength of ≥1.0MPa, a high temperature (750°C) flexural strength of ≥0.7MPa, and a thermal cycle number of 8 castings at 750°C. The product has good high temperature strength, thermal shock stability and metal scouring resistance, and does not crack or break during high temperature use. The product does not react with the melt at high temperature and can be widely used in the field of metal casting. The product has good thermal insulation performance, can ensure the consistency of process temperature, and also has good non-stick aluminum performance. DETAILED DESCRIPTION

[0027] The present invention is clearly described below in conjunction with specific embodiments, and the description herein is only used to explain the present invention, but is not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.

[0028] Example 1

[0029] The present embodiment provides a formula of an alumina foam ceramic product, including a dry material, a binder and a solvent;

[0030] The dry materials include α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder and potassium feldspar powder; the binder is aluminum dihydrogen phosphate or silica sol, and the solvent is pure water; the dry materials, calculated by weight percentage, include 60% α-alumina, 20% activated alumina, 3% kaolin, 4.5% silica powder, 2.5% dispersant, 5% mixed rare earth powder and 5% potassium feldspar powder; based on the weight of the dry materials, the binder accounts for 50% of the weight of the dry materials; based on the weight of the dry materials, the solvent accounts for 20% of the weight of the dry materials.

[0031] Among them, the particles of a-alumina are micropowder-grade particles with a particle size of 1000-2000 mesh, the particle size of activated alumina is 1000-2000 mesh, the particle size of kaolin is 500-1000 mesh, the particles of silicon micropowder are nano-grade particles with a purity of >99%, the particle size of the dispersant is 500-1000 mesh, the particle size of potassium feldspar powder is 500-2000 mesh, the particle size of mixed rare earth is 1000-2000 mesh, and the purity of mixed rare earth is >99%.

[0032] As a further measure of the present invention, the mixed rare earth powder is cerium oxide and yttrium oxide, and the mixing ratio by weight is 1:1; the dispersant is dispersant N.

[0033] This embodiment also provides an alumina foam ceramic product production process based on an alumina foam ceramic product formula, comprising the following steps:

[0034] S1, Mixture Preparation:

[0035] The weighed α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder, potassium feldspar powder, binder and solvent are sequentially fed into a ball mill, and mixed and ground in the ball mill at room temperature for 2 hours to obtain a mixture;

[0036] S2, Molding:

[0037] The mixed material obtained in step S3 is poured into a pulping machine, and a molded part is obtained by pulping and molding;

[0038] S3, Drying:

[0039] Place the molded parts in an oven to dry, keeping them at 120°C for 4 hours;

[0040] S4, sintering:

[0041] The dried molded parts are transferred to a sintering furnace for sintering and kept at 1200°C for 5 hours to obtain finished parts.

[0042] Example 2

[0043] The present embodiment provides a formula of an alumina foam ceramic product, including a dry material, a binder and a solvent;

[0044] The dry material includes α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder and potassium feldspar powder; the binder is aluminum dihydrogen phosphate or silica sol, and the solvent is pure water; the dry material, calculated by weight percentage, includes 49% α-alumina, 20% activated alumina, 5% kaolin, 5% silica powder, 1% dispersant, 10% mixed rare earth powder and 10% potassium feldspar powder. Based on the weight of the dry material, the binder accounts for 30% of the weight of the dry material; based on the weight of the dry material, the solvent accounts for 10% of the weight of the dry material.

[0045] Among them, the particles of a-alumina are micropowder-grade particles with a particle size of 1000-2000 mesh, the particle size of activated alumina is 1000-2000 mesh, the particle size of kaolin is 500-1000 mesh, the particles of silicon micropowder are nano-grade particles with a purity of >99%, the particle size of the dispersant is 500-1000 mesh, the particle size of potassium feldspar powder is 500-2000 mesh, the particle size of mixed rare earth is 1000-2000 mesh, and the purity of mixed rare earth is >99%.

[0046] As a further measure of the present invention, the mixed rare earth powder is cerium oxide and lanthanum oxide, and the mixing ratio by weight is 1:1; the dispersant is sodium silicate.

[0047] This embodiment also provides an alumina foam ceramic product production process based on an alumina foam ceramic product formula, comprising the following steps:

[0048] S1, Mixture Preparation:

[0049] The weighed α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder, potassium feldspar powder, binder and solvent are sequentially fed into a ball mill, and mixed and ground in the ball mill at room temperature for 2 hours to obtain a mixture;

[0050] S2, Molding:

[0051] The mixed material obtained in step S3 is poured into a pulping machine, and a molded part is obtained by pulping and molding;

[0052] S3, Drying:

[0053] Place the molded parts in an oven to dry, keeping them at 100°C for 4 hours;

[0054] S4, sintering:

[0055] The dried molded parts are transferred to a sintering furnace for sintering and kept at 1000°C for 6 hours to obtain finished parts.

[0056] Example 3

[0057] The present embodiment provides a formula of an alumina foam ceramic product, including a dry material, a binder and a solvent;

[0058] The dry material includes α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder and potassium feldspar powder; the binder is aluminum dihydrogen phosphate or silica sol, and the solvent is pure water; the dry material, calculated by weight percentage, includes 57% α-alumina, 15% activated alumina, 4% kaolin, 5% silica powder, 2% dispersant, 8% mixed rare earth powder and 9% potassium feldspar powder. Based on the weight of the dry material, the binder accounts for 40% of the weight of the dry material; based on the weight of the dry material, the solvent accounts for 15% of the weight of the dry material.

[0059] Among them, the particles of a-alumina are micropowder-grade particles with a particle size of 1000-2000 mesh, the particle size of activated alumina is 1000-2000 mesh, the particle size of kaolin is 500-1000 mesh, the particles of silicon micropowder are nano-grade particles with a purity of >99%, the particle size of the dispersant is 500-1000 mesh, the particle size of potassium feldspar powder is 500-2000 mesh, the particle size of mixed rare earth is 1000-2000 mesh, and the purity of mixed rare earth is >99%.

[0060] As a further measure of the present invention, the mixed rare earth powder is yttrium oxide and lanthanum oxide, and the mixing ratio by weight is 1:1; the dispersant is sodium silicate.

[0061] This embodiment also provides an alumina foam ceramic product production process based on an alumina foam ceramic product formula, comprising the following steps:

[0062] S1, Mixture Preparation:

[0063] The weighed α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder, potassium feldspar powder, binder and solvent are sequentially fed into a ball mill, and mixed and ground in the ball mill at room temperature for 2 hours to obtain a mixture;

[0064] S2, Molding:

[0065] The mixed material obtained in step S3 is poured into a pulping machine, and a molded part is obtained by pulping and molding;

[0066] S3, Drying:

[0067] Place the molded parts in an oven to dry, keeping them at 90°C for 4 hours;

[0068] S4, sintering:

[0069] The dried molded parts are transferred to a sintering furnace for sintering and kept at 1250°C for 6 hours to obtain finished parts.

[0070] Comparative Example 1

[0071] This comparative example provides an alumina foam ceramic product formula, including dry material, binder and solvent;

[0072] The dry materials include alpha-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder and potassium feldspar powder; the binder is aluminum dihydrogen phosphate or silica sol, and the solvent is pure water; the dry materials, calculated by weight percentage, include alpha-alumina 70%, activated alumina 10%, kaolin 5%, silica powder 5%, dispersant 1%, mixed rare earth powder 4% and potassium feldspar powder 5%, and the binder accounts for 40% of the weight of the dry materials based on the weight of the dry materials; the solvent accounts for 15% of the weight of the dry materials based on the weight of the dry materials.

[0073] Among them, the particles of a-alumina are micropowder-grade particles with a particle size of 1000-2000 mesh, the particle size of activated alumina is 1000-2000 mesh, the particle size of kaolin is 500-1000 mesh, the particles of silicon micropowder are nano-grade particles with a purity of >99%, the particle size of the dispersant is 500-1000 mesh, the particle size of potassium feldspar powder is 500-2000 mesh, the particle size of mixed rare earth is 1000-2000 mesh, and the purity of mixed rare earth is >99%.

[0074] The mixed rare earth powder is cerium oxide and yttrium oxide, and the mixing ratio by weight is 1:1; the dispersant is sodium silicate.

[0075] This comparative example also provides an alumina foam ceramic product production process based on an alumina foam ceramic product formula, comprising the following steps:

[0076] S1, Mixture Preparation:

[0077] The weighed α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder, potassium feldspar powder, binder and solvent are sequentially fed into a ball mill, and mixed and ground in the ball mill at room temperature for 2 hours to obtain a mixture;

[0078] S2, Molding:

[0079] The mixed material obtained in step S3 is poured into a pulping machine, and a molded part is obtained by pulping and molding;

[0080] S3, Drying:

[0081] Place the molded parts in an oven to dry, keeping them at 90°C for 4 hours;

[0082] S4, sintering:

[0083] The dried molded parts are transferred to a sintering furnace for sintering and kept at 1250°C for 6 hours to obtain finished parts.

[0084] Comparative Example 2

[0085] This comparative example provides an alumina foam ceramic product formula, including dry material, binder and solvent;

[0086] The dry materials include α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder and potassium feldspar powder; the binder is aluminum dihydrogen phosphate or silica sol, and the solvent is pure water; the dry materials, calculated by weight percentage, include 50% α-alumina, 30% activated alumina, 2% kaolin, 2% silica powder, 1% dispersant, 10% mixed rare earth powder and 5% potassium feldspar powder. Based on the weight of the dry materials, the binder accounts for 30% of the weight of the dry materials; based on the weight of the dry materials, the solvent accounts for 20% of the weight of the dry materials.

[0087] Among them, the particles of a-alumina are micropowder-grade particles with a particle size of 1000-2000 mesh, the particle size of activated alumina is 1000-2000 mesh, the particle size of kaolin is 500-1000 mesh, the particles of silicon micropowder are nano-grade particles with a purity of >99%, the particle size of the dispersant is 500-1000 mesh, the particle size of potassium feldspar powder is 500-2000 mesh, the particle size of mixed rare earth is 1000-2000 mesh, and the purity of mixed rare earth is >99%.

[0088] The mixed rare earth powder is cerium oxide and lanthanum oxide, and the mixing ratio by weight is 1:1; the dispersant is dispersant N.

[0089] This comparative example also provides an alumina foam ceramic product production process based on an alumina foam ceramic product formula, comprising the following steps:

[0090] S1, Mixture Preparation:

[0091] The weighed α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder, potassium feldspar powder, binder and solvent are sequentially fed into a ball mill, and mixed and ground in the ball mill at room temperature for 2 hours to obtain a mixture;

[0092] S2, Molding:

[0093] The mixed material obtained in step S3 is poured into a pulping machine, and a molded part is obtained by pulping and molding;

[0094] S3, Drying:

[0095] Place the molded parts in an oven to dry, keeping them at 90°C for 4 hours;

[0096] S4, sintering:

[0097] The dried molded parts are transferred to a sintering furnace for sintering and kept at 1250°C for 6 hours to obtain finished parts.

[0098] The performance indicators of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.

[0099] Table 1 (Performance indicators of Examples 1-3 and Comparative Examples 1-2)

[0100] Performance Indicators Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Room temperature compressive strength (MPa) 1.2 1.1 1.1 0.7 0.6 Flexural strength at 750℃(MPa) 0.9 0.8 1.0 0.5 0.7

[0101] It can be seen from Table 1 that, compared with Examples 1-3 of the present application and Comparative Examples 1-2, the compressive strength and flexural strength performance are significantly improved. In practical applications, the service life of the alumina foam ceramic product of the present application is greater than that of the finished product made in Comparative Examples 1-2, and it is not easy to crack or break during high-temperature use, thereby saving the production cost of the aluminum processing industry.

[0102] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A formula of an alumina foam ceramic product, characterized in that: Including dry materials, binders and solvents; The dry material includes α-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder and potassium feldspar powder; the binder is aluminum dihydrogen phosphate or silica sol, and the solvent is pure water; The dry material comprises, by weight percentage, 40-60% of a-alumina, 10-20% of activated alumina, 1-5% of kaolin, 1-5% of silica powder, 0.5-2.5% of dispersant, 5-10% of mixed rare earth powder and 5-10% of potassium feldspar powder; based on the weight of the dry material, the binder accounts for 30-50% of the weight of the dry material; based on the weight of the dry material, the solvent accounts for 10-20% of the weight of the dry material.

2. The alumina foam ceramic product formula according to claim 1, characterized in that: The a-alumina particles are micro powder particles with a particle size of 1000-2000 meshes.

3. The alumina foam ceramic product formula according to claim 2, characterized in that: The particle size of the activated alumina is 1000-2000 meshes.

4. The alumina foam ceramic product formula according to claim 3, characterized in that: The particle size of the kaolin is 500-1000 meshes.

5. The alumina foam ceramic product formula according to claim 4, characterized in that: The silicon micropowder particles are nanometer-level particles, and the purity of the silicon micropowder is greater than 99%.

6. The alumina foam ceramic product formula according to claim 5, characterized in that: The particle size of the dispersant is 500-1000 meshes, and the dispersant is dispersant N or sodium silicate.

7. The alumina foam ceramic product formula according to claim 6, characterized in that: The particle size of the potassium feldspar powder is 500-2000 meshes.

8. The alumina foam ceramic product formula according to claim 7, characterized in that: The particle size of the mixed rare earth powder is 1000-2000 meshes, and the purity of the mixed rare earth powder is greater than 99%.

9. The alumina foam ceramic product formula according to claim 8, characterized in that: The mixed rare earth powder is any two of cerium oxide, yttrium oxide and lanthanum oxide, and the mixing ratio by weight is 1:

1.

10. A process for producing an alumina foam ceramic product based on the alumina foam ceramic product formula according to any one of claims 1 to 10, characterized in that: The following steps are involved: S1, Mixture Preparation: The weighed a-alumina, activated alumina, kaolin, silica powder, dispersant, mixed rare earth powder, potassium feldspar powder, binder and solvent are sequentially fed into a mixing device, and mixed and ground in a ball mill at room temperature for 2 hours to obtain a mixture; S2, Molding: The mixed material obtained in step S3 is poured into a pulping machine, and a molded part is obtained by pulping and molding; S3, Drying: Place the molded parts in an oven to dry, keeping them at 60-120°C for 4 hours; S4, sintering: The dried molded parts are transferred to a sintering furnace for sintering, and kept at 1000-1300°C for 5-6 hours to obtain finished parts.